PENGARUH KONSELING KARIR SECARA KELOMPOK TERHADAP EFIKASI DIRI PENGAMBILAN KEPUTUSAN STUDI LANJUT PADA SISWA SMA - , Udin Yulianto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Making a career decisions is one of responsibility in the career development stage of adolescent, but many of them were still unstable to make certain about their career. Self-efficacy plays an important role in career decisionmaking. Career decision making self efficcy is as the extent to which individualsâ believe that they can evaluate themselves, collect career information, select goals, make plans, and resolve problems relevant to career decision-making. Career group counseling is one of the appropriate interventions to foster adolescent career decision making self efficacy. The aim of this study was to reveal the influence of career counseling on decision-making self-efficacy in choosing further study for high school students. Participants of the study were twelve grade students in high school (n = 20). Hypothesis of the study was career counseling can improve decision-making self-efficacy for further study of high school students. Research design used in the study was quasi-experimental which implemented untreated control group design with pretest and posttest, namely experimental research model using experimental and control group. Career counseling treatment was given to the experimental group while it was for the control group as waiting list. Both of the groups were given career decision self-efficacy scale on a week before (pretest) and a week after (posttest) the treatment was provided. The data analysis used t-test gained score. The result of this research indicated that career counseling has significantly increased decision-making self-efficacy for further study of high school students. There is significan differences studentâs in career decision-making self efficacy between experimental and control group.